# Describe how to transform the graph of f into the graph of g if f(x) = √(x - 9) and g(x) = √(x - 59).

**Solution:**

Given f(x) = √(x - 9) and g(x) = √(x - 59)

Consider g(x) = √(x - 50 - 9)

= √{(x - 50) - 9}

After transformation, this expression looks like the shifted version of f(x)

And the shifted scale is 50 units downwards

= f(x - 50)

## Describe how to transform the graph of f into the graph of g if f(x) = √(x - 9) and g(x) = √(x - 59).

**Summary:**

Therefore, we can say that by shifting f(x) by 50 downwards we get g(x), we can transform f(x) into g(x)